Centro Cultural São Paulo : programa, projeto, apropriação - Araújo, Caroline Cepeda Anseloni de (2019)
Conceived from 1975 as a necessary expansion of the Mario de Andrade Library, the Centro Cultural São Paulo - CCSP was inaugurated on May 13th,1982, during the Brazilian civilian military dictatorship, as the largest cultural center in American Latina. The building designed by the architects Eurico Prado Lopes and Luiz Benedito Castro Telles took time to be considered and architectural exponent in the city of São Paulo ; at the time of its construction , political issues were more prominent than the conceptual innovations proposed by the project, which in the field of architecture was ignored due to its experimental character, since it would not dialogue with other building from the same time. Since its inauguration, during the past thirty-seven years, CCSPbecame a powerful social, political, architectural and cultural equipment embedded in the metropolis , attuned to the historical reality of the country in different periods ans supporting the indeterminacy of the field of architecture agaist human manifestation and unpredictability. This study therefore takes place in a processof surveys and reflections towards the thematic multiplicity of the Centro Cultural São Paulo and with the transdiciplinary of the field of architecture, divided into three moments -, program conception, architectural design an the appropriation of space-, in wich three areas of knowledge are, respectively, hegemonic: history, urbanism ans sociology, understanding the project as a process constituted by several agents before and after the constructed work.